Importance and Prospects of Viticulture in Surkhandarya Region - Farkhodovich, Rakhmatov Abdukholik; uglu, Olimkulov Yashnar Mahmadamin (Universitas Muhammadiyah Sidoarjo, 2022)
This article describes the attention paid to viticulture in the country and its prospects, the ongoing projects in Surkhandarya region, especially in Altynsay district, the viticulture sector in the district, the processing of grapes and the production of products for the needs of our people. In conclusion, it is noted that the study of the characteristics of grapes and the experience of foreign countries in the development of the industry is very effective.